Status Of Non-Cultivated Food Plants In Bulamogi County, Uganda - Tabuti, J. R. S. (African Journal of Ecology, 2007)
This study was carried out to document the non-cultivated food plants (NCFPs) of Bulamogi County, Uganda. It formed part of a wider study meant to document all edible plant species in the county with the general aim of strengthening food security. The study was conducted using semi-structured interviews. Fifty-nine NCFPs were recorded in the county. These grow as weeds, wild plants and semi-cultivated crops. They are equally distributed between herbaceous (54%) and woody (46%) growth habits. They yield fruits (31, n = 59), leaves (11, n = 59) or leaves and stems (10, n = 59) for consumption. A short list of 27 NCFPs with potential for domestication is suggested here for further study.
Keywords: food security, management systems, non-cultivated food plants, Uganda